Pengaruh Literasi Keuangan dalam Model Prediksi Pilihan Karir Mahasiswa Perguruan Tinggi di Kota Pontianak - Arianto Arianto; Zulfikar Zulfikar; Tashadi Tarmizi (Eksos, 2020)
This research begins with the assumption that financial decision making is based on an understanding of financial literacy. And indicators of independent career decisions (self-employment) are used to explain and prove the truth of these assumptions. This study models the predictions of student career choices by relating it to the financial literacy amongs higher education students in Pontianak . The descriptive quantitative method was chosen as the Research method. The results of the response are processed mathematically in predictive modeling (probit-logit model) of student career choices from their relationship with financial literacy and other additional variables. The probit-logit analysis of this model was carried out with the help of statistical software, namely SPSS. The output of the research model found that knowledge of cash flow (finlit1), entrepreneurial competency variables (entshp) and risk taking confidence variables (confid) had statistical significance (<0.05) as a variable that influenced the decision for self-employment. While the independent variables are demographic variables, none of them have statistical significance to be said to influence career decisions to become self-employed. Similarly had also been found in others independent variables, which were "knowledge of asset types" (finlit2), "knowledge of insurance" (finlit3), "knowledge of investment types" (finlit4), and "knowledge of financial transactions" (finlit5).